Two‐year field analysis of reduced recalcitrance transgenic switchgrass. Issue 7 (21st April 2014) - Baxter, Holly L.; Mazarei, Mitra; Labbe, Nicole; Kline, Lindsey M.; Cheng, Qunkang; Windham, Mark T.; Mann, David G. J.; Fu, Chunxiang; Ziebell, Angela; Sykes, Robert W.; Rodriguez, Miguel; Davis, Mark F.; et al.
Summary Switchgrass (Panicum virgatum L.) is a leading candidate for a dedicated lignocellulosic biofuel feedstock owing to its high biomass production, wide adaptation and low agronomic input requirements. Lignin in cell walls of switchgrass, and other lignocellulosic feedstocks, severely limits the accessibility of cell wall carbohydrates to enzymatic breakdown into fermentable sugars and subsequently biofuels. Low‐lignin transgenic switchgrass plants produced by the down‐regulation of caffeic acid O‐methyltransferase (COMT), a lignin biosynthetic enzyme, were analysed in the field for two growing seasons. COMT transcript abundance, lignin content and the syringyl/guaiacyl lignin monomer ratio were consistently lower in the COMT‐down‐regulated plants throughout the duration of the field trial. In general, analyses with fully established plants harvested during the second growing season produced results that were similar to those observed in previous greenhouse studies with these plants. Sugar release was improved by up to 34% and ethanol yield by up to 28% in the transgenic lines relative to controls. Additionally, these results were obtained using senesced plant material harvested at the end of the growing season, compared with the young, green tissue that was used in the greenhouse experiments. Another important finding was that transgenic plants were not more susceptible to rust (Puccinia emaculata). The results of this study suggest that lignin down‐regulation in switchgrass can confer real‐world improvements in biofuel yield without negative consequences to biomass yield or disease susceptibility.